Longitudinal trends in incidence and health care use for pediatric concussion in Alberta, Canada - Wittevrongel, Krystle; Barrett, Olesya; Couloigner, Isabelle; Bertazzon, Stefania; Hagel, Brent; Schneider, Kathryn J.; Johnson, David; Yeates, Keith O.; Zwicker, Jennifer D. (Pediatric research, 2023)
Background We described longitudinal trends in the incidence of episodes of care (EOC) and follow-up care for pediatric concussion in relation to age, sex, rurality of patient residence, point of care, and area-based socioeconomic status (SES) in Alberta, Canada. Methods A retrospective population-based cohort study was conducted using linked, province-wide administrative health data for all patients <18 years of age who received a diagnosis of concussion, other specified injuries of head, unspecified injury of head, or post-concussion syndrome between April 1, 2004 and March 31, 2018. Data were geospatially mapped. Results Concussion EOCs increased 2.2-fold over the study period, follow-up visits 5.1-fold. Care was increasingly received in physician office (PO) settings. Concussion diagnoses in rural and remote areas occurred in emergency department (ED) settings more often than in metro centres or urban areas (76%/75% vs. 52%/60%). Proportion of concussion diagnoses was positively related to SES and age. Diagnosis and point of care varied geographically. Conclusions The shift in care to PO settings, increased incidence of all diagnoses, and the higher use of the ED by some segments of the population all have important implications for appropriate clinical management and the efficient provision of health care for pediatric concussion. Impact This is the first study to use EOC to describe longitudinal trends in incidence and follow-up care for pediatric concussion in relation to age, sex, rurality, point of care, and area-based SES. We report increased incidence of concussion in both emergency and outpatient settings and the proportion of diagnoses was positively related to SES and age. Patients increasingly received care for concussion in PO over time. Geospatial mapping indicated that the incidence of concussion and unspecified injury of head varied geographically and temporally. Results have important implications for appropriate clinical management and efficient provision of health care following pediatric concussion.